Outbreak of a beta-lactam resistant non-typeable Haemophilus influenzae sequence type 14 associated with severe clinical outcomes - Andersson, Madelen (BMC Infect Dis, 2015)
BACKGROUND: During October 2011 several residents and staff members at a long-term care facility (LTCF) for elderly fell ill with respiratory symptoms. Several of the residents required hospitalization and one died. Non-typeable Haemophilus influenzae (NTHi) was identified as the causative pathogen. METHODS: A descriptive analysis of the outbreak and countermeasures was performed. For each identified bacterial isolate implied in the outbreak, standard laboratory resistance testing was performed, as well as molecular typing and phylogenetic analysis. RESULTS: The identified H. influenzae was beta-lactamase negative but had strikingly high MIC-values of ampicillin, cefuroxime and cefotaxime. All isolates displayed the same mutation in the ftsI gene encoding penicillin-binding protein (PBP) 3, and all but one were identified as sequence type 14 by Multilocus Sequence Typing (MLST). In total 15 individuals in connection to the LTCF; 8 residents, 6 staff members and one partner to a staff member were colonized with the strain. CONCLUSION: This report illustrates the existence of non-typeable H. influenzae with high virulence, and furthermore emphasizes the importance of continuous surveillance of possible outbreaks in health care facilities and prompt measures when outbreaks occur.